Enhancement of the Solubility of Lipophilic Drug by Self-Micro Emulsifying Drug Delivery System (SMEDDS) For Oral Administration - Gangane, Purushottam; Singh, Kiran; Rabade, Vijaya (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: The aim of this research work is the formulation, development and evaluation of Self-Micro Emulsifying Drug Delivery System (SMEDDS). Background: Zileuton, a drug that is poorly soluble in water, was formulated with Tween 20 in a 1:1 ratio as a surfactant. F1 formulation of SMEDDS was selected from the optimum concentration of oils, surfactant, and co-surfactants from psuedoternary diagrams. Materials and Methods: Enaltec Lab in Mumbai, India, provided Zileuton as a gift sample. Raj Chemicals in India provided the eucalyptus oil. Merk Private Ltd., INDIA provided a gift sample of Tween 20. N.R. Traders, INDIA, provided polyethylene glycol 300 (PEG 300). Result: For the optimized formulations, the mean globule size of SMEDDS was found to be below 107 nm, and the zeta potential was negative. The formulations were subjected to various accelerated physical stability tests and self-emulsification evaluations. For investigating drug-excipient interactions, FTIR analysis was carried out. Zileuton in SMEDDS dissolved rapidly and completely in the phosphate buffer pH 7.4 which was used as the dissolution medium, according to the in vitro dissolution data. Conclusion: From the droplet size analysis and zeta potential values confirm the reduction in particle size to nano range which definitely improves the solubility and the dissolution rate.
Keywords: SMEDDS; Zileuton; Zeta potential